(untitled) (Editora Impacto Científico, 2025)
This article investigates Banksy’s artistic intervention on the façade of the Royal Courts of Justice in London in September 2025. The stencil, produced a few days after the arrest of 890 protesters linked to the Palestine Action group, directly confronts the British judiciary with the symbolic violence that underpins its legitimacy. The work establishes a relationship between two historical symbols: on the one hand, the modern hammer used in courts (gavel), a ritual expression of legal authority; on the other, the Malleus Maleficarum (1486), a manual for the persecution of witches that transformed the "hammer" into an emblem of repression. By reinterpreting this object, Banksy converts the hammer from an instrument of procedural closure into a sign of coercion and continuity of institutional violence. The analysis draws on the contributions of Walter Benjamin, Michel Foucault, Jacques Rancière, and Judith Butler to understand how art articulates aesthetics, politics, and historical memory. In this context, the hammer emerges as a trans-historical sign that connects different forms of legitimized violence, both in the legal sphere and in urban space, revealing the persistent tension between legality, repression, and power.